Rectal ulcer associated with SpaceOAR hydrogel insertion during prostate brachytherapy. (22nd December 2014) - Teh, Amy Y M; Ko, Hung-Ta; Barr, Gavin; Woo, Henry H
Abstract : We present a case of rectal ulceration associated with SpaceOAR hydrogel insertion during low-dose-rate (LDR) brachytherapy in a patient with prostate cancer.